Mining or Tourism: The Development Preference of Settlers Along Pagatban River in Negros Oriental, Philippines - Oracion, Enrique G. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 11 No 1 (2015), 2015)
This paper examines the development preference of settlers surveyed along the upstream, midstream, and downstream sections of Pagatban River in Negros Oriental in central Philippines. The majority of 120 respondents, equally distributed along the three sections of the river, are against the restoration of mining but are in favor of tourism development considering the ecological costs and economic benefits they have to bear with and enjoy, respectively. Specif ically, the data show that the number of respondents who do not prefer the restoration of mining is highest among downstream households while the number of those who do not prefer tourism development is highest among upstream households. The midstream respondents generally prefer both development projects. The chi-square test proves signif icant differences in the development preferences of respondents across settlements along the river. There are also significant differences in tourism preference according to the sex of the respondents, and in mining preference according to farm access, and monthly income of their households. The significant differences in household farm access and income relative to their locations further explain why economic and geographic variations result in divided preference for mining. Given that tourism development is preferred over restoration of mining, how the former’s benefits can be enjoyed across settlements should be looked into and planned with genuine community participation. Keywords: Development preference, human settlements, tourism development, restoration of mining, Pagatban River, Negros Oriental, Philippines